Implementasi Budaya 5S Untuk Penguatan Pendidikan Karakter Siswa di SMA Negeri 2 Lubuk Sikaping - Afrina, Yomita; Tamrin, M. Isnando; Rizal, Eka; Sartini, Desti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
There are still those pupils who do not have excellent character in the educational setting. As a result, the school runs a program that helps students' character development while they are in school. Through familiarization with the 5S (Smile, Greet, Greet, Polite, Polite) cultural program at SMA Negeri 2 Lubuk Suhuing, this study aims to describe the implementation of character education. It includes teachers' understanding of the nature of character education, the implementation of 5S cultural program activities, and factors that support and hinder the implementation of the 5S culture to strengthen student character education in schools. Utilizing observation, interviews, and documentation as means of data gathering, this study employs descriptive qualitative research methodologies. The principal of SMA Negeri 2 Lubuk Suhuing, curriculum representatives, instructors, and class X/XI students served as the study subjects. The steps in the data analysis approach include data reduction, data visualization, and conclusion drawing. Researchers use source triangulation, technical triangulation, and temporal triangulation as techniques for validating the veracity of their data. The study's findings indicate that SMA Negeri 2 Lubuk Suhuing uses the 5S curriculum to conduct character education. (1) Teachers are aware of the character education's nature. Learning also includes self-development activities such as routines, exemplary spontaneous actions, and conditioning, as well as 5S cultural programs. (3) The committee, the administrator, the supervisor, and every student at the school are supportive factors. In the meantime, the deterrent is that some kids continue to lack moral character because of difficult-to-manage behavior from home and other external and internal circumstances.